Marriage Services at The Office of Religious In The Pandemic Era Of Covid-19 - Heesam Dorni; Endang Larasati; Teuku Afrizal; Retno Sunu Astuti (Program Pascasarjana Universitas Negeri Makassar, 2020)
The Covid-19 pandemic has caused major changes in almost all aspects of human life, including the implementation of public services. Government policies that implement work from home (WFH) for government agencies located in areas with a certain risk of transmission, have caused public service activities to undergo changes. public services during the Covid-19 pandemic while maintaining health protocols has become a separate issue and has led to many innovations in the field of public services. One of the public services affected during the Covid-19 pandemic is marriage services at the Office of Religious Affairs (KUA). Complaints from a number of communitiesaimed at marriage services at the KUA with suspected maladministration. This study aims to analyze marriage services at the KUA during the Covid-19 pandemic. The study was conducted using the literature study method with data sources for journal articles, government agency websites and related documents. Since the beginning of the pandemic period, the implementation of marriage services at the KUA has been regulated by three circular letters from the Director General of Islamic Community Guidance at the Ministry of Religion, taking into account developments in the condition of the community. Online marriage registration is optimized, and is demonstrated by the high rate of registration of marriage registrations during the Covid-19 pandemic.